Technopreneurship Development: Entrepreneurship Ecosystem Analysis in Tasikmalaya (A Social Science and Entrepreneurship Journal, 2023)
Entrepreneurship is currently an interesting topic in academicdiscussions because it is considered a solution for a country'seconomic development. However, the entrepreneurship ratioin Indonesia is currently still very low, reaching 3.47% of thetotal population of Indonesia. This figure is still lower thanneighboring countriessuch as Singapore 8.76%, Thailand 4.26%and Malaysia with 4.74%. One area of entrepreneurship that isexpected to encourage the business ecosystem in Indonesia isthe field of technology entrepreneurship. Technopreneurshipitself refers to entrepreneurial practices that focus on thedevelopment and application of innovative technology. Itinvolves the process of creating, developing, and marketingtechnology-based products or services. Currently, the concretestep that is most likely to be taken is entrepreneurship. For thisreason, a business development model is needed that isadapted to the needs of the technology entrepreneurshipecosystem in Tasikmalaya.
Keywords: Ecosystem; Technopreneurship; Tasikmalaya